PENGARUH PEMBERIAN ABU VULKANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L. Merril) - Rahmat Hidayat; Husna Yetti; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is determining the effect of volcanic ash and get a dose of the best on the growth and production of soybean. Research has been conducted in the experimental field of the Agriculture Faculty, University of Riau from April to July 2015. The research used randomized design group, consisted of 5 treatments and 4 replications, so that there are 20 experimental units. The treatment is dose of volcanic ash 0 tons/ha, 7.5 tons/ha, 15 tons/ha, 22.5 tons/ha and 30 tons/ha. Parameters that observed were height plant, number of branches, flowering age, harvesting age, number of total pods per plant, number of full pods per plant , weight seeds per m2 and weight of 100 seeds. Data were analyzed by analysis of variance, then continued with further test with Duncan's new multiple range test at 5%. The results of research showed that giving of volcanic ash significantly take effect to height plant, number of branches, flowering age, harvesting age, number of total pods per plant, number of full pods per plant and weight seeds per m2 but the effect is not significant to the weight of 100 seeds of soybean plants. Provision of volcanic ash of 22.5 ton/ha is the best treatment against the parameters of a number of branches (9,35 branches), flowering age (31 days), harvesting age (88,5 days), number of total pods per plant (201,9 pods), number of full pods per plant (174,68 pods) and weight seeds per m2(476,61 g or 4,289 ton/ha). Keywords: Soybean, volcanic ash, growth and production.